Everything You Would Want to Know About Contracting a Tropical Disease - Welsby, Philip (Res Medica, 2014)
Why travel? To broaden the mind. Undoubtedly travel also broadens your exposure to tropical diseases. Given the current United Kingdom climate you will have to travel to get a tropical disease. This is easy given sufficient funds. You can be anywhere in the world within 36 hours. A t any one time no less than about 300,000 people are airborne. The average intercontinental jet is airborne for about 17 hours out of 24. And this is a longer proportion of life than for many birds.